PEMENUHAN HAK DAN KEWAJIBAN PASANGAN SUAMI ISTRI LONG DISTANCE MARRIAGE (LDM) DI KELURAHAN TAKOME: SUATU TINJAUAN KOMPILASI HUKUM ISLAM - Indriyani Amir; Fatum Abubakar; Harwis Alimudin (IAIN Ambon, 2026)
This study aims to analyze the practice of Long Distance Marriage (LDM) and the fulfillment of spousal rights and obligations in Takome Village, Ternate City, from the perspective of the Compilation of Islamic Law (KHI). The research uses a qualitative approach with an empirical-juridical research type, which combines the normative study of Islamic law with the social realities experienced by LDM couples. Data was obtained thru in-depth interviews, observation, and document study of eight married couples undergoing LDM, with the main background being economic factors. The research findings indicate that LDM in Takome Village varies in terms of the reasons, duration, and intensity of meetings, with the dominant motives being to earn a living, pay off debts, and build houses. Generally, the fulfillment of spousal rights and obligations is still ongoing, particularly for material support, protection, and communication, although the implementation of emotional support is limited due to distance. From an Islamic perspective, LDM can be justified as long as it is based on mutual agreement and does not disregard the fundamental obligations of husband and wife. This research confirms that the success of LDM is highly dependent on commitment, communication, and shared responsibility in maintaining household integrity. Keywords: long distance marriage, rights and obligations of husband and wife, islamic law compilation